Effects of trypanosome and helminth infections on health and production parameters of village N'Dama cattle in The Gambia - Dwinger, R.H.; Agyemang, K.; Kaufmann, J.; Grieve, A.S.; Bah, M.L. (Elsevier, 1994)
The effects of trypanosome and helminth infections on health and production parameters in 2000 village N'Dama cattle were assessed periodically. Blood examination showed Trypanosoma congolense and Trypanosoma vivax to be prevalent, while strongylid-type eggs were those most frequently encountered in faecal samples. A distinct seasonal fluctuation was detected for both blood levels of trypanosomes and helminth egg output. Strongylid burden and trypanosome infection had significant negative effects on packed red cell volume levles and body weights mainly in animals of 2-3 years old. Clear indications of an increased susceptibility ot trypanosomosis were found in animals affected by helminths. Similarly, animals infected with trypanosomes were more frequently infested with strongyles and egg counts were higher than in cattle in which no trypanosomes were detected.